Endoscopic submucosal dissection with additional radiotherapy in the treatment of T1a esophageal squamous cell cancer: randomized controlled Trial - Zhang, Yuhang; Liu, Ling; Wang, Qiming; Guo, Linjie; Ye, Liansong; Zeng, Hongze; Zeng, Xianhui; Yuan, Xianglei; Li, Yan; Zhang, Yuyan; Zhou, Elinor; Hu, Bing (Endoscopy, 2020)
Background Endoscopic submucosal dissection (ESD) is effective for treating T1a early esophageal squamous cell carcinoma (ESCC). However, occasional recurrences are inevitable. This trial was designed to clarify the efficacy of combining ESD with additional radiotherapy in the treatment of T1a ESCC.Methods Between January 2015 and September 2018, patients with early ESCC (T1aN0M0) following ESD were randomly assigned (1:1) to the radiotherapy group or non-radiotherapy group. Patients in the radiotherapy group received a median radiation dose of 59.4 Gy within 2 months after ESD. In the non-radiotherapy group, patients underwent regular follow-up only. Recurrence-free survival, cancer-specific survival, overall survival, and complications were evaluated.Results 70 patients completed the per-protocol treatment. Three patients in the non-radiotherapy group experienced intraluminal mucosal recurrence compared with none in the radiotherapy group. No local lymph node or distant metastases occurred in either group. The 3-year cumulative recurrence-free survival was 100 % in the radiotherapy group and 85.3 % in the non-radiotherapy group (P = 0.04; hazard ratio 0.08, 95 % confidence interval [CI] 0.01 – 0.86). However, there was no significant difference in RFS between the treatments within the T1a invasion subgroups (P > 0.05). No patient died in either group. Mucosal defects of more than three-quarters of the esophageal circumference were positively correlated with stenosis (P < 0.01; odds ratio 23.26, 95 %CI 4.04 – 133.86). No severe radiation toxicities were recorded.Conclusions Radiotherapy after ESD might be a safe and effective optional therapeutic strategy to prevent recurrence of T1a ESCC.